2011
DOI: 10.1111/j.1440-1789.2011.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the PDGFRA, KIT and KDR genes in glioblastoma: a population-based study

Abstract: The aim of this study was to establish the frequency of amplification of tyrosine kinase receptor genes PDGFRA, KIT and KDR (VEGFR2) at 4q12 in glioblastomas at a population level, and to assess whether such alterations have any clinical impact. Screening of 390 glioblastomas from a population-based study by differential PCR revealed amplification of the PDGFRA, KIT and KDR genes in 33 (8.5%), 17 (4.4%) and 13 (3.3%) glioblastomas, respectively. None of these alterations was prognostic for overall survival. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…Nobusawa et al [15] found the amplification of tyrosine kinase receptor gene PDGFRA in 8.3 % of GBs, and reported no significant difference between primary and secondary aGBs or between GBs with and without IDH1 mutations. Moreover, PDGFRA amplification was found more frequently in irradiation-induced HGGs and less frequently in both aGBs and pGBs, and it did not apparently affect patient survival [15].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Nobusawa et al [15] found the amplification of tyrosine kinase receptor gene PDGFRA in 8.3 % of GBs, and reported no significant difference between primary and secondary aGBs or between GBs with and without IDH1 mutations. Moreover, PDGFRA amplification was found more frequently in irradiation-induced HGGs and less frequently in both aGBs and pGBs, and it did not apparently affect patient survival [15].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, PDGFRA amplification was found more frequently in irradiation-induced HGGs and less frequently in both aGBs and pGBs, and it did not apparently affect patient survival [15]. Nobusawa et al [15] concluded that PDGFA may be implicated in the pathogenesis of a small fraction of GBs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A population based study conducted by Nobusawa et al of 390 glioblastomas using differential PCR demonstrated amplification of PDGFRA, KIT and VEGFR-2 genes in 33 (8.5%), 17 (4.4%) and 13 (3.3%) of glioblastomas respectively. None of these alterations were prognostic for overall survival (Nobusawa et al 2011). …”
Section: Cns Malignanciesmentioning
confidence: 99%